2015
DOI: 10.1177/1362361315584571
|View full text |Cite
|
Sign up to set email alerts
|

Offending profiles of individuals with autism spectrum disorder: A study of all individuals with autism spectrum disorder examined by the forensic psychiatric service in Norway between 2000 and 2010

Abstract: This study examined the characteristics of adults with autism spectrum disorder who have undergone a forensic examination and explored any relationships between the diagnosis and the offence. The reports described 41 men and 7 women. The autism spectrum disorder was diagnosed late (mean age: 25.3 years), and 22 of the 48 cases were diagnosed with autism spectrum disorder for the first time by the forensic experts. The education level and employment status were low. Family networks were close, but social networ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
54
0
2

Year Published

2017
2017
2021
2021

Publication Types

Select...
3
2
1

Relationship

1
5

Authors

Journals

citations
Cited by 44 publications
(60 citation statements)
references
References 29 publications
4
54
0
2
Order By: Relevance
“…In line with previous reports (Allen et al, 2008;Browning and Caulfield, 2011;Helverschou et al, 2015) the interviewed individuals in the present study reported various and many negative experiences with the criminal justice system (CJS). However, all six participants who had experienced custodial sentences coped well in prison.…”
Section: Discussionsupporting
confidence: 89%
See 4 more Smart Citations
“…In line with previous reports (Allen et al, 2008;Browning and Caulfield, 2011;Helverschou et al, 2015) the interviewed individuals in the present study reported various and many negative experiences with the criminal justice system (CJS). However, all six participants who had experienced custodial sentences coped well in prison.…”
Section: Discussionsupporting
confidence: 89%
“…However, most evidence suggests that individuals with ASD are less likely to offend than their peers of the same age and gender (Bjørkly, 2009;Cashin and Newman, 2009;King and Murphy, 2014). And yet, relatively little is known about the circumstances of offending in this group (Helverschou et al, 2015).…”
Section: Studies Of the Relationship Between Criminality And Asd Havementioning
confidence: 99%
See 3 more Smart Citations